Plasma Levels of Myonectin But Not Myostatin or Fibroblast-Derived Growth Factor 21 Are Associated with Insulin Resistance in Adult Humans without Diabetes Mellitus - Toloza, Freddy J. K.; Mantilla-Rivas, Jose O.; Pérez-Matos, Maria C.; Ricardo-Silgado, Maria L.; Morales-Alvarez, Martha C.; Pinzón-Cortés, Jairo A.; Pérez-Mayorga, Maritza; Arévalo-Garcia, Martha L.; Tolosa-González, Giovanni; Mendivil, Carlos O. (Frontiers in Endocrinology, 2018)
Background: Myokines are a group of protein mediators produced by skeletal muscle under stress or physical exertion. Even though their discovery and effects in cell culture and animal models of disease have elicited great enthusiasm, very little is known about their role in human metabolism. We assessed whether plasma concentrations of three known myokines (myonectin, myostatin and fibroblast-derived growth factor 21 [FGF-21]) would be associated with direct and indirect indicators of insulin resistance (IR) in individuals who did not have a diagnosis of diabetes. Methods We studied 81 adults of both sexes comprising a wide range of body adiposity and insulin sensitivity. All participants underwent a thorough clinical assessment and a 5-point oral glucose tolerance test (OGTT) with calculation of multiple IR and insulin sensitivity indices. Twenty-one of them additionally underwent a hyperinsulinemic-euglycemic clamp with determination of steady-state whole-body insulin-stimulated glucose disposal (“M”). We compared plasma myokine concentrations across quartiles of IR indices and clinical IR surrogates, and explored the correlation of each myokine with the M value. Results Plasma myonectin levels increased monotonically across quartiles of the incremental area under the insulin curve (iAUCins, higher values indicate more insulin resistance) (p-trend=0.021) and decreased monotonically across quartiles of the insulin sensitivity index (ISI – higher values indicate less insulin resistance) (p-trend=0.012). After multivariate adjustment for other relevant determinants of IR (body-mass index, age, and sex), the negative association of myonectin with ISI persisted (standardized beta= -0.235, p=0.023). Myostatin was not associated with any clinical IR indicator or direct IR index measure. In multivariate analyses, FGF-21 showed a trend toward a positive correlation with glucose disposal that did not reach statistical significance (standardized beta=0.476, p=0.091). Conclusion The secretion of myonectin may constitute an attempt at a compensatory mechanism against IR in humans.